PENGATURAN HUKUMAN MATI DALAM MATERI MUATAN UNDANG-UNDANG DIKAITKAN DENGAN PASAL 28I UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Dewi, Murti Sari; Haryono, Dodi; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The right to life is protected by the constitution inspired by human values in Pancasila, but today, in the legal system in Indonesia is still valid regarding the death penalty. It seems contradictory to the concept of humanity in Pancasila. The purpose of this thesis, namely; First, How will the death penalty in the Act in force in Indonesia, Second, Do arrangement death penalty in accordance with Article 28 of the Constitution of the Republic of Indonesia Year 1945, Third, How implications of Article 28 of the Constitution of the Republic of Indonesia Year 1945 the implementation of the death penalty in Indonesia.This type of research can be classified in this type of normative legal research , legal research literature by researching legal principles , the data source used , primary data , secondary data and data tertiary , technical analysis of legal materials in this study with qualitative analysis , outlines descriptive and emphasis on deductive method. From the research there are three main issues that can be inferred . First , setting the death penalty in law prevailing in Indonesia that the death penalty is one of the special penalty is applied cautiously , selectively majored in certain cases. Setting the death penalty in law in Indonesia can be found in the Criminal Code , Law No. 1 Year 1946 on the draft Criminal Code , Act No. 35 of 2009 on Crime Narcotics , Law Number 26 Year 2000 Crime Against Human Rights , Law No. 20 of 2001 on Corruption , Law Number 15 Year 2003 on Anti Terrorism. Second , setting the death penalty in accordance with Article 28 of the Constitution of the Republic of Indonesia Year 1945. Because of its restrictions on the death penalty should preferably be set so as not to cause inconsistency and multiple interpretations. Third , the implication of Article 28 of the Law of 1945 on the implementation of the death penalty at least will have an impact on three (3) things: first, impact against the Constitution itself , which provides for the death penalty , that it would be difficult to implement consistently because it is constrained by arrangements contained in Article 28 of the 1945 Constitution so that it is possible for citizens to make a Judicial Review against the law . Second , the emergence of legal uncertainty regarding the legality of the death penalty . Third , the impact on human rights.Keywords: Settings-Punishment die-Material Content